Effect of Xenopus laevis oocyte extract on supercoiled simian virus 40 DNA: formation of complex DNA. - Gandini Attardi, D (1976)
A soluble cell-free extract derived from stage 6 Xenopus laevis oocytes is described. From supercoiled simian virus 40 DNA the extract produces nicked circles (having a single-strand scission), linear molecules of full unit size, shorter length fragments, and various forms of complex DNA.